2012
DOI: 10.1037/a0024979
|View full text |Cite
|
Sign up to set email alerts
|

Emotional valence and physical space: Limits of interaction.

Abstract: According to the body-specificity hypothesis, people associate positive things with the side of space that corresponds to their dominant hand and negative things with the side corresponding to their nondominant hand. Our aim was to find out whether this association holds also true for a response time study using linguistic stimuli, and whether such an association is activated automatically. Four experiments explored this association using positive and negative words. In Exp. 1, right-handers made a lexical jud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 31 publications
6
88
1
2
Order By: Relevance
“…This would imply that the writing direction of a culture modulates the association of future and past with positive and negative valence. This, however, seems unreasonable, because valence is not linked to body side for right-and left-handers alike (de la Vega, De Filippis, Lachmair, Dudschig, & Kaup, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This would imply that the writing direction of a culture modulates the association of future and past with positive and negative valence. This, however, seems unreasonable, because valence is not linked to body side for right-and left-handers alike (de la Vega, De Filippis, Lachmair, Dudschig, & Kaup, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a study investigating the horizontal association between valence words and hand responses, it has been shown that the valence evaluation process is required to trigger the valence-space interactions during language processing (de la Vega, Dudschig, De Filippis, Lachmair, & Kaup, 2013;de la Vega, de Filippis, Lachmair, Dudschig, & Kaup, 2012).…”
Section: Valence Wordsmentioning
confidence: 97%
“…Online measures made available through the analysis of reaction times are needed to provide greater theoretical insight into the more immediate cognitive processes involved in the spatial representation of affect which may otherwise be masked by strategic factors in designs that focus on the end product of metaphor-based cognition (e.g., Wang, Taylor & Brunyé, 2012). Studies using response time measures have provided supporting evidence for both the 'up = good' and 'right = good' metaphors when examined in isolation (e.g., de la Vega et al, 2012Vega et al, , 2013Meier & Robinson, 2004; see review above), which suggests that this type of measure will allow us to compare the relative strength of each metaphor when the task affords their simultaneous deployment.…”
Section: Introductionmentioning
confidence: 99%
“…In right-handers, good is mapped onto the right side and bad onto the left side in a number of tasks, including diagram tasks (Casasanto, 2009;Komisky & Casasanto, 2013), lateral choices (Casasanto, 2009;Casasanto & Henetz, 2012), reaching and grasping (Ping, Dillon & Beilock, 2009), online processing (de la Vega, de Filippis, Lachmair, Dudschig & Kaup, 2012; de la Vega, Dudschig, de Filippis, Lachmair & Kaup, 2013), memory tasks , gesture (Casasanto & Jasmin, 2010), and political party evaluations (Dijkstra, Eerland, Zijlmans & Post, 2012). Like the vertical mapping of evaluation, the lateral mapping is consistent with several different experiential sources: perceptuo-motor experiences of fluency in right-handers, linguistic expressions (Bhe is my right hand^, Bhe has two left feet^) and cultural conventions, such as those establishing that shaking hands, saluting or blessing must be done with the right hand.…”
Section: Introductionmentioning
confidence: 99%